Defending to the Four Directions Evolving Uechi-ryu’s Hojoundo Exercises for Advanced Students (Revista de Artes Marciales Asiáticas, 2012)
This article introduces “Defending to the Four Directions,” techniques that add challenge to Uechi-ryu while incorporating and building upon the traditional katas which have formed the basis of the style. Making changes within a style’s training methods just to be different without any other purpose is of little value and actually destructive to the system. This article describes a meaningful and realistic addition to the practice of hojoundo, the formal exercises incorporating basic movements. “Defending to the Four Directions” is intended for advanced students who have mastered Uechi-ryu’s foundamentals. In addition, the practice is well-suited for adaptation and adoption into other martial art styles.